Mobile Plus Expressways Travel Assistant Assistant System (M-PEX) - Anny Rozana, Mohd Faizal Kim (2009)
Most frequent PLUS Expressways users found it was difficult for them to access point-of-need information (e.g. toll fare, RSA, Touch ‘n Go and etc.) while travelling on the expressways. Currently, the only way to do so was through the web based application.Thus, the purpose of this study is to develop a mobile application, Mobile PLUS Expressways Travel Assistant System (M-PEX) that will be able to assist PLUS Expressways users by providing on the spot information. M-PEX will focus on five main functions which are toll fare calculation, travel duration calculation,facilities,services provided by PLUS and PLUS user guide. M-PEX was developed using Rational Unified Process (RUP) methodology. A user acceptance testing and evaluation has been high reliability of M-PEX’s ability to assist user by providing on the spot information. They also show some interesting differences in user response between the users who owns transportation and users who does not owns transportation, due to differences in the frequency of using PLUS Expressways.